Electrolyte disorders in a young female following short-term omeprazole therapy - Amadi, Collins; M. Owamagbe, Emmanuel; S. Duru, Ugochukwu (International Journal of Basic & Clinical Pharmacology, 2018)
A 29 years old female presented to us in the metabolic clinic of the University of Port Harcourt Teaching Hospital (UPTH) on account of a week history of easy fatigability, weakness, and lower extremity muscle cramps associated with numbness and tingling sensation in the peri-oral area, fingers and toes. Two weeks prior to the onset of her presenting symptoms, she had visited a local pharmaceutical shop on account of a distressing epigastric discomfort and was subsequently placed on daily oral omeprazole 20mg daily for a month by a pharmacist. She had been on the omeprazole medication for two weeks before her present symptoms manifested. Her past medical history was not suggestive of hypoparathyroidism nor pancreatitis. She was married with three children and has an uneventful family, social and obstetric histories. On examination, she was a healthy well-oriented young female with positive Trousseau’s, Chvostek’s and epigastric tenderness signs. Further Laboratory evaluation revealed she had low plasma magnesium, low plasma albumin-corrected calcium, and low serum parathyroid hormone levels, while other laboratory parameters were essentially normal. A diagnosis of omeprazole-induced electrolyte disorders (hypomagnesaemia and hypocalcaemia) associated with hypoparathyroidism was made following the review of her clinical examination and laboratory findings. She was subsequently managed with oral magnesium supplements following the withdrawal of the omeprazole medication (replaced with oral ranitidine), monitored weekly, and full recovery was achieved after three weeks.